Phenotypic characterization of indigenous chicken populations in Southeastern Oromia Regional State of Ethiopia. (8th December 2014) - Negassa, Deneke; Melesse, Aberra; Banerjee, Sandip
Summary The objective of this study was to characterize the native chickens reared in three agro-ecological zones of Southeastern Oromia Regional State of Ethiopia. Data on visual appraisal and linear body measurements were obtained from a total of 600 matured local chickens of both sexes drawn from 240 households. The results indicated that the average flock size, age at first egg of hens and eggs produced per clutch were 11.9 heads, 6.2 months and 15.4 eggs, respectively. The majority of the male chicken possessed snake head shape (60.7 percent) and most of them had rose combs (57.9 percent), red feather plumage (46.1 percent), yellow shanks (86.3 percent), red earlobes (84.2 percent) and yellow skin (56.8 percent). Majority of the hens possessed single combs (43.5 percent), red earlobes (77.3 percent), yellow shanks (44.4 percent), yellowish brown feather (27.4 percent) followed by red (24.2 percent) and black (21.2 percent). The cocks were generally heavier (1.39 kg) than the hens (1.22 kg). The average values for breast angle (degrees), body length, body width, shank length, shank circumference, keel bone length, wing span, comb length and beak length of the cocks were 45.9, 24.1, 24.9, 7.43, 3.86, 9.63, 7.99, 4.86 and 1.91 cm, respectively. The corresponding values for the hens were 40.2, 22.7, 23.8, 7.43, 3.46, 8.95, 7.40, 2.47 and 1.71. The values for wing span, comb length, beak length, body weight, breast angle and keel bone length differed (P < 0.05) across the agro-ecologies. The best predictor for assessing the body weight of hens was breast angle and body length, whereas in the cocks it was best estimated using breast angle and shank circumference values. The present study suggests that indigenous chickens in the study area possess useful economic traits that could be improved through systematic breeding for enhanced productivity under scavenging production systems.